Compound odontoma - José Marcelo Vargas Pinto; Fábio Augusto Coelho de Oliveira; Cláudio Ferreira Nóia; Wagner Humberto Martins dos Santos (Faculdade São Leopoldo Mandic, 2008)
Odontomas are the most common types of odontogenic tumors, as they are considered more as a developmental anomaly (hamartoma) than as a true neoplasia. The aim of the present study is to describe a clinical case of compound odontoma, analyzing its most commonsigns, its region of location, the decade of life and patient's gender, disorders that may occur as well as the treatment proposed. In order to attain this objective, the method was description of the present clinical case and bibliographic revision, arriving at the result that the treatment for this type of lesion invariably is surgical removal (enucleation and curettage) and the prognosis is excellent. The surgical result was followed up in the post-operative period by radiographic exam, and it was possible to conclude that there was complete cicatrization and tissue repair.